(untitled) (Anwer Khan Modern Medical College Journal, 2015)
Liver Fibrosis (LF) is a common outcome in chronic liver disease (CLD). Over a period of time, the process results in cirrhosis leading to disruption in functional capacity of liver. Further serious complications may occur including portal hypertension, liver failure and cancer. The magnitude of CLD has increased being recognized as a major cause for morbidity and mortality globally and it is increasing progressively in Bangladesh also. Question arises "Is the transabdominal needle biopsy of liver, the traditional reference standard method, sufficient and efficient enough for detecting and assessing liver fibrosis particularly in the early stages of significant liver disease?" More simpler, convenient and less expensive blood tests such as ’Enhanced Liver Fibrosis (ELF) immunoassay test’, Fibrotest and Aspartate transaminase-platelet ratio index (APRI), have been developed and reported for identification of significant CLD and use as prognostic tool in clinical practice. Among them, the ELF test had been found to be statistically the best for diagnosing and predicting clinical outcomes in patients with CLD and may be a useful prognostic tool in clinical practice. This ELF immunoassay test has been briefly reviewed in this article. Short title: ELF immunoassay test for CLD Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 38-41